1976
DOI: 10.1099/00221287-95-2-249
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity Titration of Guinea-pig Inclusion Conjunctivitis Agent in Irradiated McCoy Cells

Abstract: Estimation of the infectivity of the agent of guinea-pig inclusion conjunctivitis for irradiated McCoy cells, assayed as inclusion-forming units, was influenced by the age of cells after irradiation, the maturation time of the inclusions, the centrifugal force and the centrifugation temperature. Agent passaged through irradiated McCoy cells or guinea-pig conjunctivae showed a greater capacity to infect irradiated McCoy cells without centrifuging than agent grown in a chick embryo. The nature of the change and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Furthermore, it has been noted that successive passage in cell cultures resulted in an 'adaptation', i.e. rapid development of the intracellular bacterium, and also acquisition of greater infectivity to the cell cultures than when grown in chick yolk sac (Griffiths et al, 1976). However, during passage of the trachomaderived C. trachomatis strains in McCoy cell cultures, there was no detectable alteration in the major antigens (Gordon et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been noted that successive passage in cell cultures resulted in an 'adaptation', i.e. rapid development of the intracellular bacterium, and also acquisition of greater infectivity to the cell cultures than when grown in chick yolk sac (Griffiths et al, 1976). However, during passage of the trachomaderived C. trachomatis strains in McCoy cell cultures, there was no detectable alteration in the major antigens (Gordon et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugation facilitates chlamydia1 infection, at least in part, by greatly increasing attachment; this may range from 5-to 7-fold, as with MRC4f, to more than 100-fold with other chlamydiae (Stirling & Richmond, 1977;Griffiths et al, 1976). The facilitation occurs, not through sedimentation of organisms, but from induced cell surface changes (Allan & Pearce, 1979), which may explain the failure of antibody to inhibit attachment in centrifugeassisted infection.…”
Section: Discussionmentioning
confidence: 99%
“…bovine serum (growth medium), harvested, irradiated and monolayers were prepared as previously described (Griffiths et al, 1976); monolayers were used 24 to 96 h after irradiation of cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously developed a quantitative assay for infectivity of the guinea-pig inclusion conjunctivitis strain (GP-IC) of C. psittaci using centrifugation to enhance infection of irradiated McCoy cell monolayers (Griffiths et al, 1976). We found that organisms passaged through monolayers or the guinea-pig conjunctiva showed a greater capacity to infect static monolayers (spontaneous infection) than organisms grown in the chick embryo.…”
Section: Introductionmentioning
confidence: 99%